Bebas Mual Muntah Akibat Kemoterapi dengan Terapi Komplementer pada Pasien Kanker Payudara - Santi Manurung; Dewi Irawaty (Journal of Telenursing (JOTING), 2021)
This study aims to identify various complementary therapies that can overcome nausea and vomiting in breast cancer patients receiving chemotherapy. The method used is a literature search from different online databases. The results showed several complementary therapies to treat nausea and vomiting in breast cancer patients receiving chemotherapy, such as acupressure, yoga, acupuncture, foot massage therapy, breathing exercises and guided imagery combined with progressive muscle relaxation. In conclusion, several complementary therapies are significantly effective in overcoming nausea and vomiting in breast cancer patients receiving chemotherapy. Keywords: Breast Cancer, Nausea Vomiting, Complementary Therapy